Looting Africa: the Economics of Exploitation - Bond P.; Bond Patrick (London New York Zed Books, 2006)
Despite the rhetoric, the people of Sub-Saharan Africa are become poorer. From Tony Blair's Africa Commission, the G7 finance ministers' debt relief, the Live 8 concerts, the Make Poverty History campaign and the G8 Gleneagles promises, to the United Nations 2005 summit and the Hong Kong WTO meeting, Africa's gains have been mainly limited to public relations. The central problems remain exploitative debt and financial relationships with the North, phantom aid, unfair trade, distorted investment and the continent's brain/skills drain. Moreover, capitalism in most African countries has witnessed the emergence of excessively powerful ruling elites with incomes derived from financial-parasitical accumulation. Without overstressing the "mistakes" of such elites, this book contextualises Africa's wealth outflow within a stagnant but volatile world economy.
Keywords: 330